2012
DOI: 10.1179/1743132811y.0000000065
|View full text |Cite
|
Sign up to set email alerts
|

Compensatory remodeling in symptomatic middle cerebral artery atherosclerotic stenosis: a high-resolution MRI and microemboli monitoring study

Abstract: In patients with symptomatic middle cerebral artery atherosclerotic stenosis, MESs were observed more frequently in the PR group than in the non-PR group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
30
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 22 publications
6
30
1
Order By: Relevance
“…Most VW-MR imaging studies 20,61 have found that MCA remodeling was (on average) outward in symptomatic plaques and inward in asymptomatic plaques, though some studies 16 have found no significant difference. Microembolic signals on transcranial Doppler sonography were more common in patients with MCA atherosclerotic plaque with VW-MR imaging evidence of positive remodeling, 65 consistent with the idea that positive remodeling is characteristic of the higher risk plaque that produces thromboembolism.…”
Section: To Assess Atherosclerotic Plaque Activitysupporting
confidence: 62%
“…Most VW-MR imaging studies 20,61 have found that MCA remodeling was (on average) outward in symptomatic plaques and inward in asymptomatic plaques, though some studies 16 have found no significant difference. Microembolic signals on transcranial Doppler sonography were more common in patients with MCA atherosclerotic plaque with VW-MR imaging evidence of positive remodeling, 65 consistent with the idea that positive remodeling is characteristic of the higher risk plaque that produces thromboembolism.…”
Section: To Assess Atherosclerotic Plaque Activitysupporting
confidence: 62%
“…Vulnerable plaque components are associated with a high degree of positive remodeling because of which ischemic events often result from a plaque without significant stenosis. 27,28 Not only the plaque burden but also plaque distribution has clinical relevance. In patients with subcortical infarcts adjacent to the proximal middle cerebral artery, superior wall plaques are more likely to be symptomatic because they are nearer to the orifices of penetrating arteries ( Figure 1B).…”
Section: Advanced Vascular Imaging and Additional Sonographic Studiesmentioning
confidence: 99%
“…13 Other study showed that microembolic signals on transcranial Doppler were observed more frequently in patients with positive remodeling of MCA. 19 Moreover, BOD often is lumped in with non-BOD as ICAS, 20,21 or only BOD-type ICAS (eg, paramedian pontine infarcts) 22 was studied in most studies. To the best of our knowledge, no previous study has specifically compared the vascular pathophysiologies in terms of vascular remodeling and plaque characteristics between 2 types of ICAS.…”
Section: Ryoo Et Al Differential Vascular Pathophysiologies Of Icas 2819mentioning
confidence: 99%